2018
DOI: 10.1002/aic.16196
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water saturation on gas slippage in circular and angular pores

Abstract: A unified model for gas slip flow through circular and angular pores in both single phase flow and two-phase flow conditions is developed, and the effect of water saturation on gas slippage factors in different pore shapes are revealed. For circular pores, the water saturation retains as thin film binding on pore surfaces without changing the shape of the cross section, and the hydraulic diameters continuously reduce as water saturation increases, directly leading to an increase in the slippage factor. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…[22][23][24] Notably, during the long geological evolution process of shale gas/oil reservoirs, it can be demonstrated that regular circular nanopores are hardly existed in realistic shale matrix. [25][26][27] Unfortunately, a commonly used assumption is made in almost all the current research about shale gas/oil reservoirs, that is, pore shape in shale matrix is regarded as circles, which is inconsistent with the real situation and will result in a dramatic discrepancy. According to the aforementioned context, for related industries about nanoconfined water flow, it can be demonstrated that little research has been implemented to investigate water transport through nanopores with irregular cross-sections.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] Notably, during the long geological evolution process of shale gas/oil reservoirs, it can be demonstrated that regular circular nanopores are hardly existed in realistic shale matrix. [25][26][27] Unfortunately, a commonly used assumption is made in almost all the current research about shale gas/oil reservoirs, that is, pore shape in shale matrix is regarded as circles, which is inconsistent with the real situation and will result in a dramatic discrepancy. According to the aforementioned context, for related industries about nanoconfined water flow, it can be demonstrated that little research has been implemented to investigate water transport through nanopores with irregular cross-sections.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to studying nanopores with cross-sections, Wu et al proposed a gas migration model in shale reservoirs composed of nanopores with rectangular cross-sections and described continuous flow and slip flow through cross-sectional shape factors. Li et al [57] show that the shape of the pores affects the distribution of water film and the mechanism of gas slip. Liang et al [58] found that there is no regular circular cross-section in the shale matrix, and most nanopores have elliptical cross-sections.…”
Section: 22mentioning
confidence: 99%
“…A literature search shows that three flow mechanisms have mainly been considered in apparent permeability models of shale matrix: surface diffusion (Wasaki and Akkutlu, 2015;Wang and Marongiu-Porcu, 2015;Wu et al, 2016b;Wu et al 2016c;Wu et al2016d;Wu et al 2017;Sun et al, 2017;Zhang L. et al, 2018;Jia et al, 2019), Knudsen diffusion and slip flow (Sakhaee- Pour and Bryant, 2012;Akkutlu and Fathi, 2012;Xiong et al, 2012;Sheng et al, 2015;Zhang et al, 2015;Song et al, 2016;Li et al, 2019). Stress sensitivity (Dong et al, 2010;Pang et al, 2017;Cui et al, 2018a;Cui et al, 2018b), the water film thickness (Li et al, 2016;Sun et al, 2017;Li et al, 2018;Peng et al, 2018) and adsorption layer thinning (Li et al, 2020) are the three main factors affecting the pore radius. A few scholars believe that the matrix shrinkage effect (An et al, 2017;Sheng et al, 2019) has a certain impact on the porosity and apparent permeability of shale matrix, but the influence degree of matrix shrinkage is not clear enough.…”
Section: Introductionmentioning
confidence: 99%